KONFLIK INTERNAL TOKOH UTAMA DALAM NOVEL MENGURAI RINDU KARYA NANG SYAMSUDDIN - Aimifrina, Aimifrina (Jurnal KATA, 2017)
The purpose of this study is to determine the internal conflict of the main character in the novel of Mengurai Rindu by Nang Syamsuddin. Internal conflict is a conflict insidethe heart of a character(characters in the story). The main character is categorized as important figures and shown continuously so dominating most of the story. Therefore, a conflict which wants to know is an internal conflict experienced by Lela.The theory used in this study is the theory of Jones, while the method is descriptive method. The internal conflict inside the novel of Mengurai Rindu by Nang Syamsuddin was sadness, disappointment, truthful, and sympathy. Internal conflicts such as sadness and disappointment happened between Lela with Angku Datuk, AngkuSutan, teachers whose teaching with Lela, and Gunawan. Meanwhile sympathy happened between Lela and Gunawan.